Fine Motor Skills and Lexical Processing in Children and Adults - Winter, Rebecca E.; Stoeger, Heidrun; Suggate, Sebastian P. (Frontiers in Psychology, 2021)
Children’s fine motor skills (FMS) link to cognitive development, however, research on their involvement in language processing, also with adults, is scarce. Lexical items are processed differently depending on the degree of sensorimotor information inherent in the words’ meanings, such as whether these imply a body-object interaction (BOI) or a body-part association (i.e., hand, arm, mouth, foot). Accordingly, three studies examined whether lexical processing was affected by FMS, BOIness, and body-part associations in children (study 1, n = 77) and then adults (study 2, n = 80; study 3, n = 71). Analyses showed a differential link between FMS and lexical processing as a function of age. Whereas response latencies indicated that children’s FMS were associated with ‘hand’ words, adults’ FMS linked to the broader concept of BOI. Findings have implications for shared activation theories positing that FMS support lexical processing.